GE_GERICHTE C/13536/2017 vom 2. Februar 2018 - GE Cour de justice (2018)
MAINLEVÉE PROVISOIRE ; PRESCRIPTION ; INTERRUPTION DU DÉLAI ; ACTE DE DÉFAUT DE BIENS ; RECONNAISSANCE DE DETTE | LP.82; CO.135